BEYOND THE SCALE: COMPREHENSIVE TREATMENT OPTIONS FOR YOUTH OBESITY - Magdalena Jabłonowska; Paulina Grzeszczuk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: This review aims to examine the multifactorial nature of childhood obesity by exploring its prevalence, diagnostic standards, and associated metabolic and psychological complications, as well as evaluating current strategies for management.Materials and Methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using the following keywords: “childhood obesity”, “obesity treatment”, “Mediterranean diet”, “DASH diet”. physical activity”, “liraglutide”, “semaglutide”, “phentermine-topiramate”, “setmelanotide” and “bariatric surgery”.Summary: Childhood obesity is a growing global issue with serious health consequences that often persist into adulthood. It stems from multiple factors like diet, activity levels, and environment. Healthy diets (e.g., Mediterranean, DASH) and at least 60 minutes of daily physical activity are key for prevention and treatment. Medications like GLP-1 receptor agonists (e.g., liraglutide, semaglutide) may help in severe cases, while bariatric surgery is an option for extreme, treatment-resistant obesity. Effective management requires a combination of lifestyle changes and medications.      Conclusions: Combating childhood obesity requires a personalized approach combining lifestyle changes, nutrition education, physical activity, and, when needed, medication or surgery. Early intervention is vital to reduce long-term health risks and psychological effects. Treatment should involve multidisciplinary teams, including pediatricians, dietitians, psychologists, and specialists. Future efforts must improve public health policies, promote healthy environments, and conduct long-term studies on treatments. Continued innovation in diagnosis and prevention is essential to tackle this growing epidemic and improve children's quality of life.